Hidden in plain sight: Uncovering the emotional labor of Black women students at historically White colleges and universities. - Kelly, Bridget T.; Gardner, Paige J.; Stone, Joakina; Hixson, Ashley; Dissassa, Di-Tu (Journal of Diversity in Higher Education, 2021)
We utilized the emotional labor triangle to understand how 16 Black women students who attended Historically white colleges and universities (HWCUs) navigated gendered-racialized oppressive environments that mattered to their academic success. This study contributes to a gap in the literature, as much of the research focused on students of color without disaggregating for gender or other social identities. In addition, the literature is scant on experiences of Black women students use of emotional labor. Emotional labor has largely been studied from a management perspective. Through qualitative semi-structured interviews, we examined the emotional labor Black women expended while pursuing their undergraduate degree. We employed a qualitative, intersectional, methodological approach to foreground historically marginalized voices and situated the study in the hypervisibility Black women participants described feeling as space invaders on their historically White undergraduate campus and at the same time the invisibleness of their voice and masking of their feelings as they encountered gendered racism. Further, we emphasized the emotional toll and stress that may occur for Black women when they do not utilize engaged coping mechanisms while expending their emotional labor. The study holds implications for educators to address emotional labor inequities within HWCUs. (PsycInfo Database Record (c) 2021 APA, all rights reserved) © 2019 National Association of Diversity Officers in Higher Education
Number: 2
Keywords: amériques; approches et analyses; care; colère; femmes universitaires noires*; intersectionnalité; projet charge mentale; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; travail émotionnel; violences; états-unis

Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap